Experimental Analysis of SMART Scrubbing System with the Principle of Dynamic Precipitation - Ravindran, Nirvenesh; Hasini, Hasril (International Journal of Engineering and Technology, 2018)
This paper presents an experimental investigation of a SMART scrubbing system in sugar processing plant. The objectives are to address the problem and develop new technique to increase the efficiency and eliminate sugar sludge production downstream of process line. The SMART scrubbing effect of water with the principal of dynamic precipitation was conducted on-site with calculated flow rate, which simulates the SMART scrubbing system. The on-site and scaled-down model experiments measure the upstream and downstream dust concentration and processes the flow rate of water required to counter the dust concentration based on the feedback flow. The investigation was conducted with a steady airflow of 6 m3/s with variation of water flow rates. The result of the on-site studies shows an excellent increase in average and maximum efficiencies of 98.77% and 99.3% respectively.